2014
DOI: 10.4321/s0004-05922014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Parámetros genéticos para caracteres productivos y reproductivos en Holstein y Jersey colombiano

Abstract: El objetivo de este estudio fue estimar parámetros genéticos y fenotípicos en caracterís-ticas productivas y reproductivas en ganado Holstein y Jersey de Antioquia, Colombia. La información fue obtenida de 85 hatos lecheros de raza Holstein y 7 hatos de raza Jersey, ubicados en 18 municipios del Departamento de Antioquia. Las características productivas evaluadas fueron: producción de leche (PL), porcentaje de proteína (PP), porcentaje de grasa (PG) y puntaje de célu-las somáticas (SCS) y las características r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
2
4
Order By: Relevance
“…These results coincide with those indicated by Solarte & Zambrano (2012) for the Holstein breed in Nariño. On the other hand, Zambrano et al (2014) found DA values below those obtained in this research for Holstein cows in Antioquia. In relation to services per conception, the results of farms F1, F2 and F4 are similar to those reported by Zambrano et al (2014).…”
Section: Results and Discusioncontrasting
confidence: 92%
See 1 more Smart Citation
“…These results coincide with those indicated by Solarte & Zambrano (2012) for the Holstein breed in Nariño. On the other hand, Zambrano et al (2014) found DA values below those obtained in this research for Holstein cows in Antioquia. In relation to services per conception, the results of farms F1, F2 and F4 are similar to those reported by Zambrano et al (2014).…”
Section: Results and Discusioncontrasting
confidence: 92%
“…The reproductive efficiency of the herds evaluated does not bear similarity in similar contexts of cattle farms in the high altitude tropics of Colombia, being, in the case analyzed, manifestly lower. The mean of the CI and DA does not coincide with the results reported by Zambrano et al (2019) and Zambrano et al (2014) for conditions in Antioquia. The open days obtained in all the herds were above the range considered optimal for Holstein cows, which causes a significant increase in economic losses and an increase in the discard rate since this is an important indicator of the reproductive efficiency of the herd.…”
Section: Results and Discusioncontrasting
confidence: 84%
“…The low heritability (0.16±0.02) exhibited for milk yield does not concur with the result from other studies investigating the Jersey breed (Gacula Jr. et al, 1968;Deb et al, 1974;Ahlborn and Dempfle, 1992;Campos et al, 1994;Visscher and Goddard, 1995;Musani and Mayer, 1997;Roman and Wilcox, 2000;Guo et al, 2002;Dionello et al, 2006;Missanjo et al, 2013;Zambrano et al, 2014). The values reported in these studies hovered between 0.21 and 0.46.…”
Section: Discussioncontrasting
confidence: 87%
“…PP is reported by several authors to be one of the traits with the highest heritability, with values commonly close to or greater than 0.3 (Zambrano et al, 2014;Rincón et al, 2015) or even reaching values between 0.47 and 0.65 (Makgahlela et al, 2013;Zhao et al, 2015;Gebreyesus et al, 2016), and this trait is less affected by environmental effects than milk production is (Lipkin, Bagnato, & Soller, 2008a). The heritability found for PP with the random regression model was 0.29, surpassing that reported by other authors (Khanzadeh, Hossein, & Naserani, 2013); however, it is important to highlight that few reports on heritability of protein percentage use this methodology; random regression has typically been used to model protein content rather than protein percentage (De Roos, Harbers, & De Jong, 2004;Caccamo et al, 2008;Múnera, Herrera, Gonzáles, Henao, & Cerón, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that SCS is a trait of low heritability (Zambrano et al, 2014;Costa, Santos, Cobuci, Thompson, & Carvalheira, 2015); however, in this study, values were high in all models (0.27, 0.28 and 0.22 for BLUP, M-BLUP and RRM, respectively) and close to those reported by some other authors (Kheirabadi & Alijani, 2014). It is also noteworthy that previously published values are closer to the random regression results in this study, with reports ranging from 0.18 to 0.22 (Liu, Reinhardt, & Reents, 2000;Mrode & Swanson, 2004).…”
Section: Resultsmentioning
confidence: 99%